BLIS graduates' perceptions on the BLIS program and the alumni support community (2011)
Presents the perceptions of the BLIS graduates of UP SLIS from 1997 to 2011 as to the relevance and sufficiency of the BLIS program. Also utilizes their perceptions to provide inputs in building an Alumni Support Community.